Muscle damage response in female collegiate athletes after repeated sprint activity - Keane, K. M.; Salicki, R.; Goodall, S.; Thomas, K.; Howatson, G. (The Journal of Strength and Conditioning Research, 2015)
Exercise-induced muscle damage (EIMD) is a well-investigated area, however there is a paucity of data surrounding the damage response in females. The aim of this study was to examine the damage responses from a sport-specific bout of repeated sprints in female athletes. Eleven well-trained females (mean ± SD; age: 22 ± 3 years; height: 166.6 ± 5.7 cm; mass: 62.7 ± 4.5 kg) in the luteal phase of the menstrual cycle completed a repeated sprint protocol designed to induce EIMD (15 × 30 m sprints). Creatine kinase, countermovement jump height, knee extensor maximal voluntary isometric contraction (MVIC) force, delayed onset muscle soreness (DOMS), 30-m sprint time, and limb girth were recorded before, after, 24, 48, and 72 hours after exercise. Creatine kinase was elevated at 24, 48, and 72 hours (p = 0.05), peaking at 24 hours (+418%) and returning toward baseline at 72 hours. Countermovement jump height was reduced immediately after, 24, and 48 hours (p = 0.05). Sprint performance was also negatively affected immediately after, 24, 48, and 72 hours after exercise. Muscle soreness peaked at 48 hours (p < 0.01) and remained significantly elevated at 72 hours after exercise (p < 0.01). Limb girth and MVIC did not alter over time. This study provides new information on the EIMD response in trained females after a sport-specific bout of repeated sprints. Importantly, this damage response has the potential to negatively affect performance for several days after exercise.